Development of sport tourism in Panji Anom village, Buleleng regency, Bali - Syarif Hidayat; Wasti Danardani; Hendra Mashuri (Universitas Sriwijaya, 2023)
Sports tourism is a promising business in the future, especially in Indonesia after the COVID-19 pandemic. The concept of sports tourism is to carry out tourism activities by exercising, where sports are believed to be a means to maintain and even increase the immunity of the human body. The concept of sports tourism will be beneficial for both physical and spiritual aspects. Sports tourism is one type of special interest tourism. Currently, sports tourism has become a trend, and the government's attention to increasing the country's foreign exchange is echoed by the government the theme of the National Sports Day (Haornas 2020) in sports science, sports tourism, and the sports industry. Reflecting on this, it is appropriate for the Indonesian sports academy to continue to innovate through research, one of which is in the field of sports tourism. This research is development research in the second stage which has the target of producing a module that can be used in the implementation of tourism sports activities in the village of Panji Anom, Buleleng Regency. The method used is a modified ADDIE (Analysis-Design-Development-Implementation-Evaluation) model development concept. The results of the study indicate that the draft module that has been compiled has been tested by experts and is declared to be used with revision